Analysis of Various Damping Models in The Simulation of the Seismic Response of Structures in the STARK ES Software - V. N. Simbirkin; Yu. V. Panasenko; V. V. Kurnavin (Железобетонные конструкции)
When performing structural calculations for dynamic loads including seismic impacts, the STARK ES software package allows to implement various damping models. In this paper, a comparative analysis of three types of the damping models used to increase the calculated seismic resistance of structures is carried out. These are the models of nonlinear viscous dampers, in which the reactive force depends non-linearly on the velocity of the rod movement, equivalent (for an energy dissipated) linear-viscous dampers and equivalent (for a maximum force and an energy dissipated) elastic – perfectly plastic elements. As an example, an analytical model of the structural system of a projected building on a site with a seismicity of more than 8th intensity level is used.